MANAJEMEN PENDIDIKAN INKLUSIF DI SEKOLAH MENENGAH PERTAMA - Dewi Puji Lestari, Fitria (Jurnal Pendidikan Khusus, 2017)
ABSTRACT : The purpose of this study was to describe the management of inclusive education in SMPN 4 Sidoarjo which includes: management of learners, currculum management, learning process management, management of educators and management of facilities. This qualitative research using descriptive qualitative. In conclusion, the management of inclusive education in SMPN 4 Sidoarjo includes, 1) student management begins with the existence of new student acceptance planning through activity analysis of requirement of earners. Implementation of acceptance of students with special needs through the inclusion path that is carried out by referring to the mechanism and registration requirements contained in the guidelines for the implementation of student enrollments Sidoarjo. 2) curriculum management related to the development of using curriculum 2013 modified in accordance with the ability and condition of learners. 3) management of learning process in inclusive class begins with learning plan that is analysing the cometence based, indicators, lesson plan by modifying the concepts. Stucturally the learning exercises are implemented as stated in the lesson plan by modifying the concepts and evaluation for students with special needs include 3 aspect of evaluation that is, attitude, knowledge and skills to the ability of learners. 4) management of educators associated with the planning of spesialized educators begins with a record of the needs of teachers for students with special needs. Then the school held a recruitment and selection teacher assistant. 5) management of facilities negins with analysis needs of facilities needed by buyying. In general the availability of facilities in inclusive school is sufficient with the resource center, therapy room, special learning media and learning aids.   Keywords: Management, Inclusive Education.